PUBLIC DEBATE ABOUT THE CONDITION OF THE MAPUCHE - Millacura Salas, Claudio (Revista de Historia Social y de las Mentalidades, 2014)
During the first months of the Ricardo Lagos Escobar government (2000-2006), this prompted several measures in favor of Indigenous People. Soon those measures were rejected by the most conservative part of chilean society. One of its major representative in the area of history, by means of letters published released by the favorite newspaper of the sector, not only took charger of delegitimize the actions taken by the government but also the demands of indigenous people. This dispute beyond align the chilean society following the tenets of each one of the positions, exposed the ideology that fuels the economic system in Chile and their advocates. Mapuche